ANALISIS PENGARUH REALISASI ANGGARAN PENDAPATAN DAN BELANJA DAERAH TERHADAP INDEKS PEMBANGUNAN MANUSIA STUDI PADA KABUPATEN TULANG BAWANG - Alfattah, Dhiwa Abiyu; Hudani, Muhammad Mufti; Purwaningsih, Vitriyani Tri; Sobita, Nindya Eka (Politeknik Bisnis Indonesia, 2024)
The Human Development Index (HDI) is one of the indicators used to measure the success of development in an area. The primary objective of this research is to examine the extent to which the implementation of the Regional Budget has contributed to the improvement of the Human Development Index in Tulang Bawang Regency, Anggaran Pendapatan dan Belanja Daerah (APBD), on HDI in Tulang Bawang Regency during the 2012-2023 period. The research employed secondary data obtained from the Badan Pusat Statistik (BPS). The study utilized multiple linear regression with an Ordinary Least Squares estimation. Considering that the effects of APBD realization cannot be felt directly, this research uses a time lag. The dependent variable in this research is the HDI of Tulang Bawang Regency, while the independent variables consist of Pendapatan Asli Daerah (PAD), Dana Alokasi Umum (DAU), and Dana Alokasi Khusus (DAK) which represent the realization of the APBD. The study results fund that the realization of Pendapatan Asli Daerah (X1) and Dana Alokasi umum (X2) has a positive and significant influence on the Human Development Index (HDI) of Tulang Bawang Regency (Y), with a confidence level of 95%. Meanwhile, for DAK variable, its effect on HDI in Tulang Bawang Regency. Keywords: Human Development Index (HDI), Dana Alokasi Khusus, Tulang Bawang